Pengaruh Koneksi Politik, Dewan Komisaris dan Karakteristik Perusahaan terhadap Penghindaran Pajak (Perusahaan BUMN Yang Terdaftar di Bursa Efek Indonesia) - Hijriani, Anisa Nadia; Latifah, Sri Wahjuni; Setyawan, Setu (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this research is to test whether politic connections commissioners and characteristic’ companies can influence tax avoidance which is done by the companies. Object of thisresearch is all of the BUMN companies from various sectors which are listed in IndonesianStock Exchange 2011-2013. The data which is used is secondary data directly obtain from BEIwebsite and each of companies website by using documentation technique. The data is analyzedby using double regression analysis method and hypotheses test. Based on the result of the testwhich is done in this research, it shows that all of independent variables do not influence towardthe tax avoidance, either through Gaap ETR or Current ETR. With the t-test of political connections, the average attendance, Roa, DER and firm size have no effect on tax evasion as measuredby ETR and Current ETR Gaults, but the number of board meetings negatively affects the taxevasion measured by Current ETR partiallyKeywords:Political connection, commissioners, characteristic of companies, and tax evasion